2005
DOI: 10.2166/wst.2005.0716
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of wastewaters and valorisation of by-products from “Serpa” cheese manufacture using nanofiltration

Abstract: Second cheese whey (SCW) is a by-product of cheese and curd cheese production that is usually not recovered and therefore contributes substantially to the negative environmental impact of the cheese manufacture plants. Membrane technology, namely nanofiltration (NF), is used in this work for the recovery of SCW organic nutrients, resulting from "Serpa" cheese and curd production. The SCW is processed by NF to recover a rich lactose fraction in the concentrate and a process water with a high salt content in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Table 3 presents the linear regression lines (with 95% confidence intervals and correlation coefficients) used for the determination of pure water permeability and the MWCO of NF membranes. The hydraulic permeability is also close to that obtained from other researchers [37,38] for membranes with the same reference and with similar operating conditions.…”
Section: Resultssupporting
confidence: 89%
“…Table 3 presents the linear regression lines (with 95% confidence intervals and correlation coefficients) used for the determination of pure water permeability and the MWCO of NF membranes. The hydraulic permeability is also close to that obtained from other researchers [37,38] for membranes with the same reference and with similar operating conditions.…”
Section: Resultssupporting
confidence: 89%
“…Some studies have already been carried out for the use of the SCW ( Table 6 ), but the information available is still scarce. As examples, we can refer the use of SCW for the production of fermented drinks with prebiotics and probiotics (symbiotic drinks) [ 8 ], for the production of lactose by crystallization [ 97 ], for lactic acid production [ 14 ] or for the obtention of bioethanol by yeast fermentation [ 16 , 22 , 37 ].…”
Section: Proposed Methodologies For Valorization Of Second Cheese Whey (Scw)mentioning
confidence: 99%
“…Membrane technology, namely NF was used for the recovery of SCW organic nutrients, resulting from Serpa cheese and curd cheese production. It was reported that the NF operation can reduce the wastewater organic load and simultaneously contribute to the valorization of the cheese and curd cheese manufacture by-products [ 97 ]. Table 6 summarizes the main conclusions of the reports regarding the valorization and characterization of second cheese whey.…”
Section: Proposed Methodologies For Valorization Of Second Cheese Whey (Scw)mentioning
confidence: 99%
“…Two NF membranes (NFT50 and HR-95-PP) were characterized and tested. It was reported that the NF operation can reduce the wastewater organic load and simultaneously contribute to the valorization of the cheese and curd cheese manufacture by-products [89]. [95]…”
Section: Proposed Methodologies For Valorization Of Second Cheese Whey (Scw)mentioning
confidence: 99%